Pengembangan Media Komik Digital Pada Mata Pelajaran IPAS Topik Memakan Dan Dimakan (Rantai Makanan) Kelas V Di SDN Jatirejo - Al Muflihah, Nadia; Nuruddin, Muhammad (IJPSE Indonesian Journal of Primary Science Education, 2024)
The development of science and technology is progressing very rapidly, so that human knowledge and skills will continue to develop as time goes by. Merdeka Belajar is a new policy program of the Ministry of Education and Culture of the Republic of Indonesia (Kemendikbud RI) which was launched by the Minister of Education and Culture of the Republic of Indonesia, Advanced Indonesia Cabinet, Nadiem A Karim. Education aims to develop knowledge, understanding, skills and mastery of concepts that can be applied in life. Comics are a learning media tool that functions to convey learning messages. However, the printed comic learning media used in the learning process is currently less popular among students. Therefore, media is needed that can minimize the shortcomings of printed comics and provide students with mastery of concepts applied through digital comics. The aim of this research is to develop digital comic learning media. Through digital comic learning media for fifth grade elementary school students. Apart from that, this research also aims to determine the development process and validity of the media. The type of development research used is the ADDIE model which goes through five stages, namely analysis, design, development, implementation and evaluation. The subjects in the research were class V students for the 2023/2024 academic year. Material and media validity data collection techniques use validation questionnaire sheets to measure media quality as well as teacher and student questionnaire response data. Based on the process of media development trial results through 5 stages, namely the initial stage (analysis), this stage carries out problem analysis, student analysis, material analysis and setting learning objectives. The second stage (design) includes planning material preparation, product selection and media product design format selection. The third stage (develop) is the process of developing media creation, validation by material experts and media experts, and verification. The fourth stage (implementation) is carried out to determine learning outcomes and students' responses to the learning media that has been developed. The fifth stage (evaluate) is the evaluation stage to review and improve learning media. Based on the research results, quality learning media results were obtained.